Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2556963
|View full text |Cite
|
Sign up to set email alerts
|

Effects of balancing for physical abilities on player performance, experience and self-esteem in exergames

Abstract: Game balancing can help players with different skill levels play multiplayer games together; however, little is known about how the balancing approach affects performance, experience, and self-esteem-especially when differences in player strength result from given abilities, rather than learned skill. We explore three balancing approaches in a dance game and show that the explicit approach commonly used in commercial games reduces self-esteem and feelings of relatedness in dyads, whereas hidden balancing impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 21 publications
3
72
1
Order By: Relevance
“…Our findings suggest that we need to adopt a more differentiated view. While smaller performance differences could be offset through balancing strategies [12], we also observed that differences in cognitive abilities influenced players' abilities of understanding game rules and subsequently achieving ingame goals. Although we pre-empted some issues through the breadth of games we offered, our results raise the question whether any game can be made accessible for all players, and what alternative approaches to accessible game design could look like.…”
Section: Designing For Diversity -Does One Game Fit All?mentioning
confidence: 62%
“…Our findings suggest that we need to adopt a more differentiated view. While smaller performance differences could be offset through balancing strategies [12], we also observed that differences in cognitive abilities influenced players' abilities of understanding game rules and subsequently achieving ingame goals. Although we pre-empted some issues through the breadth of games we offered, our results raise the question whether any game can be made accessible for all players, and what alternative approaches to accessible game design could look like.…”
Section: Designing For Diversity -Does One Game Fit All?mentioning
confidence: 62%
“…Previous research has also examined player balancing, but only in a limited number of situations (e.g., [5,11,16,20]). For example, recent studies have shown that player balancing can be effectively applied in 2D and 3D shooting games [5,20].…”
Section: Introductionmentioning
confidence: 99%
“…The fourth category of research explores the playful self, which is a self characterized by aspects of life, such as engagement (Lindtner, Mainwaring, Dourish, & Wang, 2009), fun, enjoyment and immersion (Gerling, Miller, Mandryk, Birk, & Smeddinck, 2014;Gonzales, Finley, & Duncan, 2009;Hwang, Holtzman, & Resnick, 2011;Mekler, Bopp, Tuch, & Opwis, 2014). Although the notion of play is sometimes connected to gaming, it is vital to separate the two.…”
Section: The Playful Selfmentioning
confidence: 99%
“…Changes might occur, but such changes often are seen as epiphenomenal to the self, rather than something that affects the fundamental, ontological constitution of the self. For example, in analyzing the effects of interaction, several researchers discussed emotional changes (e.g., Gerling et al, 2014;Panger, 2014;Toma, 2010), cognitive changes (e.g., Fox et al, 2013;Vasalou et al, 2007) or behavioral changes (e.g., Fox et al, 2013;Laschke et al, 2011;Maitland & Chalmers, 2010;Yarosh, 2013). Yet, although emotions, cognition, and behavior are important components of the self, one can question whether these three aspects alone constitute the self.…”
Section: The Stable Coherent Individual Selfmentioning
confidence: 99%